Maya Lin - A Strong Clear Vision - Lee Mock, Freida; Lenzer, Don; Marritz, Ed (New Video, 2003)
This Academy Award winner reveals the contentious origins of the Vietnam Veterans Memorial and tells the inspiring story of its creator, a 21-year-old Yale architecture student. Beating out some of the most prestigious architecture firms from around the world, Lin's plan was selected from over 1,000 different designs, a giant victory for such a young and unknown artist. But little did Maya Lin know that her battle was just beginning. In Washington, to defend her design, Lin came up against a mighty opposition, challenging indignant veterans and a hostile Congress to ultimately prevail with her emotional "wall". And what began as one of the country's most bitterly disputed public monuments became one of the world's most inspirational and frequently visited memorials. In this riveting and dramatic portrait, renowned filmmaker Freida Lee Mock combines interviews and archival footage to chronicle Lin's story-from it's origins, dominated by her David vs. Goliath battle over the Vietnam Veterans Memorial, to a career designing other memorials, always with an innate talent, and resolute courage. [Cover]